Realization of Green Engineering at ETUT - Serdar Gedayev; Yslam Orazov (Universitas Diponegoro, 2023)
Despite being one of the young universities in the country, Oguz han Engineering and technology university of Turkmenistan (ETUT) aims to integrate all sustainable development goals in all aspects of its education and research programs within the scope of “Green Engineering.